Teaching Metacognitive Strategies in Reading through CALLA to Non-English Major Students in a Vietnamese University - Hau Thi Huynh (Vietnam Journal of Education, 2024)
Since the 1990s, several studies on teaching metacognitive methods to improve reading comprehension have been undertaken worldwide. However, learners’ views regarding using a specific model of metacognitive strategy instruction in reading, which adds to the success of teaching metacognitive methods, have not yet received much attention, particularly in Vietnam. This research is an attempt to fill that gap. This study investigates the learners’ attitudes towards training metacognitive strategies through the Cognitive Academic Language Learning Approach (CALLA) model in reading. To achieve this aim, the author carried out a mixed-methods design study on 52 non-English-majored participants at a university in Vietnam. The research tools involve an attitudinal questionnaire and group interviews. The findings of this study reveal that the employment of the CALLA model in teaching metacognitive strategies received neutral to positive attitudes from most students. However, the instruction itself exposed some shortcomings that must be addressed. In addition, some statistical differences were found in the cognition of high and low language proficiency groups. Based on the findings, some specific recommendations have been made for teachers and learners in teaching metacognitive strategies.